Imported technology and manufacturing employment in Ethiopia - Haile, Getinet; Srour, Ilina; Vivarelli, Marco (Springer, 2016)
There is a dearth of research on the impact of technological change over employment in least developed countries (LDCs) embarking on globalization and consequent international technological transfer. Using a panel of 1,940 Ethiopian firms over the period 1996–2004 and deploying GMM-SYS estimates, this paper aims to establish the role played by trade, FDI and technology in affecting employment and skills. The results obtained lend support to a labour–augmenting effect. Moreover, the implemented two-equation dynamic framework provides evidence of a skill-bias specific to those enterprises with higher share of foreign ownership and located in the vicinity of the capital city.